The Legal Politics of Outsourcing and Its Implication for the Protection of Workers in Indonesia - Siti Kunarti; Nur Putri Hidayah; Hariyanto Hariyanto; Muhammad Bahrul Ulum (Faculty of Law, Sriwijaya University, Indonesia, 2024)
This research aimed to analyse where the legal politics concerning outsourcing in Indonesia's legal system by scrutinizing its regulation in Book III of the Civil Code and enforcement of the Government Regulation in lieu of Law concerning Job Creation Law Number 6/2023, with its following implication to protect workers at the national level. This research employed doctrinal legal research on legal instruments related to outsourcing with statutory, conceptual, and historical approaches. The research showed that legal politics concerning outsourcing had experienced dynamic congruence with the political configuration when the legislative product on outsourcing was made. The differences emerge where outsourcing is not restricted to certain occupations in Book III of the Civil Code of Indonesia. However, Law Number 13/2003 restricted the definition of outsourcing to occupations not related to core businesses. Law Number 11/2020 and Government Regulation Number 35/2021 fit employers. Both laws govern the legal protection for outsourced employees with the transfer of undertaking to protect employment regarding changing vendors with the condition that the jobs are still available. Meanwhile, the type of work outsourced is unlimited, resulting in a deficit compared to the previous norm.